(untitled) (Vietnam Journal of Community Medicine, 2021)
Objective: To evaluation of the short-term results of treatment of patients with chronic lower extremity artery disease (ACD) due to atherosclerosis by iliac-femoral endovascular intervention. Methods: Interventional study was conducted on 116 patients with chronic lower extremity artery disease who underwent endovascular intervention at the iliac-femoral level at the Institute of Cardiology in 2016-2017. Result: There were 88.8% of the study subjects (103/116 people) successfully intervened. Death is a fairly common complication with 6 cases during hospital stay, 5 cases in the first 3 months and 12 cases in 6 months after the intervention. The rate of improvement of Fontain stage after treatment is high, reaching over 70% after 3 months. Walking distance and ABI increased significantly over time after the intervention compared to before. The ultrasound results showed that after the intervention, most of the cases of foot reperfusion improved and had complete recanalization, while a small percentage detected thrombosis at the intervention site. The rate of limb preservation after 3 months was 95.5% and maintained until the end of the study. Conclusion: Treatment of chronic lower extremity artery disease by iliac-femoral endovascular intervention gives positive results.